Demographic and clinical characteristics of children with juvenile dermatomyositis in Cape Town - Okong'o, Lawrence Owino (Division of Rheumatology, 2015)
Study rationale: Juvenile dermatomyositis (JDM) is a rare idiopathic inflammatory myopathy of childhood with an incidence of 1.9-3.2 per million. The aetiology of JDM is uncertain but may result from immune dysregulation triggered by environmental factors in genetically susceptible children. The demographic and clinical characteristics of JDM may thus differ by race and geographic regions. Few studies have described the characteristics of JDM patients from Africa. There is need for further studies for better understanding of the epidemiology, clinical characteristics and outcome of patients with JDM from the continent. Methods: We conducted a retrospective observational study to determine clinical characteristics and outcomes of patients satisfying the Bohan and Peter criteria for probable JDM seen between 2004-2013 in Red Cross, Groote Schuur and Tygerberg hospitals in Cape Town. Data was analyzed using R version 3.1.0 (2014-04-10). Results: Twenty-five cases were identified: 16 female and 9 male. Thirteen (52%) of the cases were of indigenous African, eleven (44%) mixed and one (4%) European ancestry. The median ages at disease onset and diagnosis were 6.75 (range 2.0-9.7) and 7.9 (range 3.4-9.75) years respectively. Muscle weakness and characteristic cutaneous manifestations occurred in all the 25 patients while 24 had elevated muscle enzymes. All the patients received corticosteroids, seventeen (73.9%) received methotrexate and four received rituximab. Eleven patients had calcinosis during the disease course [median follow up period of 50 (range 0.5-159) months]. The mortality was 2/25 (8%) while only 40% of the patients had clinically inactive disease by PRINTO criteria. There was no difference in racial distribution (p-value = 1), age at disease onset (p-value = 0.87) and disease duration prior to treatment initiation (p -value = 0.75) between patients who had clinically active and inactive disease. Discussion: The demographic characteristics of children with JDM were similar to that from most other regions of the world with female predominance and similar age at onset. The median delay in diagnosis (4 months) was not longer than that reported in most other studies. However, some children had prolonged delay of up to 7 years due to misdiagnosis that denied them appropriate treatment in a timely manner. Majority (60%) of the patients also remained with clinically active disease, which put them at risk of further disease complications including calcinosis. Even though the mortality rate was low (8%) this was still more than double that reported in most recent large studies especially from the resource rich countries. Conclusions: Long-term follow up of JDM patients is advisable since majority of patients seem to have clinically active disease many years after disease onset despite treatment. Formulation and use of appropriate treatment guidelines and protocols may aid in the early diagnosis and appropriate management for optimum outcomes.